Identity and stammering: negotiating hesitation, side‐stepping repetition, and sometimes avoiding deviation. Issue 7 (2nd April 2013) - Butler, Clare
Abstract: Individuals who experience speech dysfluency are often stigmatised because their speech acts differ from the communicative norm. This article is located in and seeks to further the identity debates in exploring how individuals who are subject to the intermittent emergence of a stigmatised characteristic manage this randomised personal discrediting in their identity work. Through a series of focus groups and semi‐structured interviews participants grudgingly report their management approaches which include concealing, drafting in unwitting others, role‐playing and segregating self from their stammer. In describing how they manage their stammer they detail their use of the social space in a number of ways, including as a hiding place; a site for 'it' (the stammer); a gap in which to switch words; and a different area in which to perform. This study offers important insights, increasing our understanding of the often hidden negotiations of identity work and the sometime ingenious use of space in the management of a social stigma.